Bochdalek Hernia in Asymptomatic Adults: A Case Report of Radiological Importance (Journal of Bangladesh College of Physicians and Surgeons, 2018)
Congenital Diaphragmatic Hernias (CDH) is a rare entity with incidence of 1:3000 live births. Late presentation is unusual and in most cases is diagnosed in adolescents or early childhood. Asymptomatic diaphragmatic hernia in the absence of trauma is very rare in adults. The finding of CDH in adults is mostly incidental. Left sided hernia i.e. Bochdalek hernia is more common. It is more commonly associated with other anomalies. The morbidity and mortality are mainly due to pulmonary hypoplasia. We report a case of CDH, posterolateral defect (Bochdalek type), with mild mediastinal shifting to right side in a young lady, who was asymptomatic throughout the life and referred to us for evaluation of incidental findings of chest X-ray abnormality who was suffering from cholelithiasis. The surgical approach for the resolution of this pathology is variable and it depends on the presence and severity of visceral complications.J Bangladesh Coll Phys Surg 2018; 36(4): 175-178